Restoration of UPK1A-AS1 Expression Suppresses Cell Proliferation, Migration, and Invasion in Esophageal Squamous Cell Carcinoma Cells Partially by Sponging microRNA-1248 - Du, Fang (Cancer Manag Res, 2020)
BACKGROUND: Recent evidence suggests that long non-coding RNAs (lncRNAs) are emerging as key determinants of esophageal squamous cell carcinoma (ESCC) progression. This study aimed to investigate the role of lncRNA UPK1A antisense RNA 1 (UPK1A-AS1) in ESCC cell proliferation, invasion, and migration. METHODS: The expression levels of UPK1A-AS1 and miR-1248 were determined using quantitative reverse transcriptase-polymerase chain reaction. The functional role of UPK1A-AS1 in ESCC was investigated using subcellular localization assay, Cell Counting Kit-8 assay, colony formation assay, scratch-healing assay, and transwell invasion assay. The functional interaction between UPK1A-AS1 and miR-1248 was assessed using luciferase reporter and RNA pull-down assays. RESULTS: Twenty dysregulated lncRNAs were detected in ESCC. Downregulation of UPK1A-AS1 was observed in ESCC tissues and cell lines. Functionally, upregulation of UPK1A-AS1 suppressed the proliferation, migration, and invasion of ESCC cells. Moreover, an inverse correlation between UPK1A-AS1 and miR-1248 expression was observed in ESCC specimens, and miR-1248 was identified as a direct target of UPK1A-AS1. Furthermore, we found that UPK1A-AS1 exerts its anti-cancer effects partially through sponging miR-1248 in ESCC cells. CONCLUSION: UPK1A-AS1 suppressed the proliferation, migration, and invasion of ESCC cells partially by sponging miR-1248. Hence, our findings provide novel insights into the regulatory pathway involved in ESCC development.